Resilience and enculturation: Strengths among young offenders with Fetal Alcohol Spectrum Disorder - Rogers, Billie; McLachlan, Kaitlyn; Roesch, Ronald (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Fetal Alcohol Spectrum Disorder (FASD) is a lifelong disorder with no cure and is accompanied by neurological deficits. FASD is a health concern that is increasingly gaining attention within the justice system. Research has identified an association between delinquency and prenatal alcohol exposure. This study looked at resources of resilience for young offenders and addressed questions regarding the association between enculturation and resilience, and whether offence histories differed between youth with and without a diagnosis of FASD. Ninety-four young offenders between 13 and 23 years of age participated, 47 diagnosed with FASD and 47 without. While this study was not intended to be a study on Aboriginal adolescence, given the overrepresentation of FASD among Aboriginal youth involved in justice settings, the Multigroup Ethnic Identity Measure (MEIM) was included to assess levels of enculturation among youth. The Child and Youth Resilience Measure (CYRM) was used to assess resilience. Results showed a positive association between the resilience-enhancing resources and enculturation, indicating that the two are intricately connected. Neither group differed in their rates on the resilience-enhancing resources or the enculturation measure. While the resilience measure was not significantly associated with official conviction data, it did demonstrate significant associations with self-reported offending data. Finally, no significant results emerged to suggest that FASD had an influence on the association between the resilience measure and offence history or the enculturation measure and offence history. Findings suggest the importance of incorporating cultural components into services targeted to produce resilience and positive outcomes, and that different groups may have different service needs.